Experimental and molecular dynamic simulation of supercooling phenomenon of sodium acetate trihydrate. (June 2023) - Sun, Mingyang; Liu, Tong; Li, Mulin; Liu, Tianze; Wang, Xinlei; Chen, Guijun; Jiang, Dongyue
Abstract: Sodium acetate trihydrate (SAT) is commonly employed as phase change material for thermal storage due to its low cost, large phase transition enthalpy and suitable temperature range for domestic heating. However, the supercooling property of SAT makes it distinctive to commonly used phase change materials ( e.g. paraffin wax). The supercooling of the SAT could be a "rapier". In some occasions, the supercooling is unfavorable for rapid heat releasing, while in some circumstances the supercooling facilitates the long-term thermal storage without the requirement on thermal insulation. The supercooling phenomenon of SAT is of great interest and importance without proper explanation. This work analyzes and explains the supercooling phenomenon of SAT during phase change process from the perspectives of experiment and molecular dynamics simulation. The result indicates that the supercooling of the SAT is mainly determined by the strong electrostatic interaction between sodium anions and acetate cations induced ions aggregation in the cooling process. The ions aggregation blocks the water molecules to form a crystal structure and induce supercooling effect. The purpose of this paper is to provide a basis for the future application of SAT for thermal energy storage systems. Highlights: The supercooling of sodium acetate trihydrate was explained by molecular dynamics. An ion aggregation mechanism was proposed for explaining the supercooling effect. The effects of supercooling degree of sodium acetate trihydrate were investigated.